Advanced control of power converters : techniques and Matlab/Simulink implementation /: techniques and Matlab/Simulink implementation. (2023) - Komurcugil, Hasan; Bayhan, Sertac; (Professor), Guzman, Ramon; (Electrical engineer), Malinowski, Mariusz; Abu-Rub, Haithem
No abstract available